A clinico mycological study of tinea pseudoimbricata - M Bhagyashree; P Shilpashree (Wolters Kluwer Medknow Publications, 2022)
Introduction: Tinea pseudoimbricata is a variant of dermatophytosis characterized morphologically by concentric scaly rings resembling tinea imbricata with an culture isolate other than Trichophyton concentricum. To date, no large case report series is available. Aim: To study the clinical profile and the fungus isolated in patients with tinea pseudoimbricata. Materials and Methods: In this case series, all the patients with tinea imbricata with an isolate other than Trichophyton concentricum were subjected to a detailed history and clinical examination. Scrapings of the scales were investigated with potassium hydroxide examination and culture in Sabouraud Dextrose Agar enriched with cycloheximide and chloramphenicol. The results obtained were tabulated and analyzed. Results: A total of 42 patients fulfilling the above culture criteria were included in the present study. A majority were in the age group of 21-40 years (54.70%) with a male preponderance (M:F = 2:1). All the patients had abused steroids for more than 4 weeks and had multiple site involvement. Trichophyton tonsurans (42.8%) was the predominant isolate cultured, followed by Trichophyton mentagrophytes. Conclusion: Hence, as per our study, tinea pseudoimbricata is encountered more often nowadays due to the misuse of topical steroids and to diagnose tinea pseudoimbricata culture is mandatory. The morphology of concentric rings is not restricted to Trichophyton concentricum, but can occur with other species depending on the clinical scenario.